Two new species of Tydeidae (Acari: Prostigmata) associated with stingless bees - Da-Costa, Tairis; Rodighero, Luana Fabrina; Da Silva, Guilherme Liberato; Ferla, Noeli Juarez; Blochtein, Betina (Zootaxa, 2019)
Tydeid mites have a cosmopolitan distribution and are associated with diverse substrates such as soil, plants, stored products, and animals like vertebrates and insects. Here we report two new species of tydeid mites living inside stingless bee colonies in Brazil. Lorryia meliponarum n. sp. and Melissotydeus bipunctata n. sp. are described and illustrated, and in addition a key to the species of Melissotydeus is presented.